Performance of Eclipse Farm test coupled with e-Reader for screening antibiotics in sheep and goat’s milk - Giraldo J.; Cabizza R.; Sanz D.; Mata L.; Molina M.P. (Innovation for sustainability in sheep and goats, 2019)
The presence of antibiotic residues in milk is a concern due to technological and health reasons. Although various methods have been developed to analyse antibiotic residues in cow milk, such methods do not always work correctly with sheep and goat’s milk. Herein, we present a study of the performance of a new system for the screening of antimicrobial residues in sheep and goat’s milk. The method combines a microbial inhibitor test (Eclipse Farm) and a device (e-Reader) that integrates incubation at 65ºC and continuous monitoring of the change in colour. The performance of the new system was validated according to European Commission Decision 2002/657/EC. Sensitivity of the new system was evaluated on 12 molecules from several families of antimicrobials. The detection limits were close to European maximum residue limits (MRL). Detection capabilities (CCβ) were also determined for 7 molecules representing the main antimicrobial groups used in dairy husbandry (penicillins, cephalosporins, aminoglycosides, tetracyclins, sulphonamides and macrolides). Most of the molecules were detected at MRL level. The Eclipse Farm test coupled to e-Reader has shown to be a valuable tool for screening a broad-spectrum of antimicrobial residues in sheep and goat milk.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)